The Construction of Al-'Uqud Al-Murakkabah in the Hawalah Contract from the Perspective of Islamic Law and Indonesian Positive Law - Moh. Asep Zakariya Ansori; Ryan Nasruddin (al-Afkar, Journal For Islamic Studies, 2026)
This research comprehensively discusses the construction of Al-'Uqud Al-Murakkabah in the context of hawalah contract from the perspective of Islamic law and Indonesian positive law. The primary focus of this study is on identifying and analyzing the multi-contract elements involved in debt transfer, as regulated in the DSN-MUI fatwa. The research identifies four main multi-contract models frequently applied in hawalah transactions, namely the combination of Qard, Bai' al-Wafa', Murabahah, and other variation forms such as Ijarah Muntahiyah bi Tamlik. From an Islamic law perspective, this study evaluates the compatibility of these multi-contract models with Sharia principles, including the prohibition of gharar, riba, and the fulfillment of contract conditions and pillars. Meanwhile, from the perspective of Indonesian positive law, the research discusses regulations, implementation mechanisms, and the legal validity of debt transfer within the national legal system, including its relation to Civil Law and related regulations. The research results indicate that the existence of multi-contracts in hawalah transactions presents unique challenges, both in terms of Sharia compliance and harmonization with Indonesian positive law. The study emphasizes the importance of an integrative approach between Sharia principles and the national legal system to create a clearer and more applicable legal foundation. Additionally, the research recommends the creation of a specific fatwa regarding multi-contract law, capable of addressing contemporary economic needs while maintaining the sustainability of Sharia principles. These findings are expected to contribute to the development of hawalah contract practices in Indonesia and serve as a reference for policymakers and Islamic economic practitioners.